TOURISM AND INTERNATIONAL RELATIONS. FACTORIES THAT INFLUENCE TO THEM TOURISM INDUSTRY PROMOTION - Teshaboyeva Nafisa Zubaydulla qizi; Aliyeva Saida Aziz qizi (Ta’lim innovatsiyasi va integratsiyasi, 2025)
Annotation This article analyzes the complex relationship between tourism and international relations. It examines the role of diplomacy, political stability, economic factors, cultural exchange, and technological advancements in promoting the tourism industry. The study also explores how globalization and the concept of soft power allow countries to enhance their international image and attract more tourists. Practical examples and policy recommendations for sustainable tourism development are provided.